2021
DOI: 10.2215/cjn.16091020
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive Dysfunction and Gait Abnormalities in CKD

Abstract: Background and objectivesCognitive impairment is a major cause of morbidity in CKD. We hypothesized that gait abnormalities share a common pathogenesis with cognitive dysfunction in CKD, and therefore would be associated with impaired cognitive function in older adults with CKD, and focused on a recently defined gait phenotype linked with CKD.Design, setting, participants, & measurementsGait assessments and neuropsychological testing were performed in 312 nondisabled, community-dwelling older adults (aged … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…The progressive aging-associated muscle atrophy, which frequently presents with muscle weakness and slow motion, is the most common type of muscle atrophy observed in humans ( 39 ). With aging, the risk of both CKD and declining capacities such as reduced strength and cognition increases ( 40 ); this risk is maximized in subjects developing “accelerated biological aging” ( 41 ). Sensory–motor functioning is very common in frail individuals who are at highly vulnerable for loss of independence in activities of day living, fall and mortality ( 42 ).…”
Section: Aging and Common Kidney Disease Comorbidities Which Impair Mpsmentioning
confidence: 99%
“…The progressive aging-associated muscle atrophy, which frequently presents with muscle weakness and slow motion, is the most common type of muscle atrophy observed in humans ( 39 ). With aging, the risk of both CKD and declining capacities such as reduced strength and cognition increases ( 40 ); this risk is maximized in subjects developing “accelerated biological aging” ( 41 ). Sensory–motor functioning is very common in frail individuals who are at highly vulnerable for loss of independence in activities of day living, fall and mortality ( 42 ).…”
Section: Aging and Common Kidney Disease Comorbidities Which Impair Mpsmentioning
confidence: 99%
“…Gait speed, for example, is simple to measure, takes less than 1 min to complete, and is associated with both functional and cognitive outcomes [ 3 , 9 ]. In addition, our work and that of others have identified other abnormalities of gait among adults with CKD [ 10 , 11 ]; these are present even among individuals with preserved gait speed and are associated with elevated risk of falls and development of cognitive impairment, the latter of which can further exacerbate fall risk [ 10 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 59%
“…Our findings are in line with a recent publication demonstrating gray matter atrophy in brain regions in control of gait and cognition in CKD patients. This study, furthermore, identified a gait phenotype specific to CKD patients that was distinct from established neurological gaits ( 80 ).…”
Section: Discussionmentioning
confidence: 79%
“…It seems that renal disease patients have much worse gait variability in the temporal domain measures, e.g., ST, but similar characteristics in the spatial measures (SL), compared to the healthy elderly ( 61 ), to middle aged patients on HD ( 47 ), and to neurological patients ( 26 ). Different regions of the brain are associated with different spatio-temporal gait parameters ( 79 ), and in CKD mainly the pre-frontal, frontal, and temporal cortexes are affected by gray matter atrophy ( 80 ), which may explain these differences. At first sight it seems not to be logical to compare our renal disease patient data with optimal thresholds derived from healthy and neurological patients.…”
Section: Discussionmentioning
confidence: 99%